Dead girls don't lie - Wolf, Jennifer Shaw (Scholastic, 2015)
Jaycee and Rachel were best friends until a terrible night when their friendship faltered and Rachel was found dead, but her last text message starts Jaycee on a search that may prove Rachel's death was no random crime.